PESISIR BERDAYA: Pemberdayaan Masyarakat Melalui Skrining, Edukasi, dan Pendampingan Self-Management Diabetes Melitus Berbasis Komunitas - Ceria Nurhayati; Nuh Huda; Christina Yuliastuti; Dedi Irawandi; Nur Muji Astuti; Imroatul Farida; Dul Majid; Sri Wahyu Wilujeng; Andan Peristika Didayana9 (Universitas Merdeka Surabaya, 2026)
Diabetes mellitus (DM) is a non-communicable disease whose prevalence continues to increase, including in coastal communities with limited access to health services and information on disease management. Low awareness of early detection and the implementation of diabetes self-management has the potential to increase the risk of complications. Therefore, community-based community empowerment efforts are needed through screening, education, and ongoing mentoring. This community service activity aims to increase the knowledge, awareness, and ability of coastal communities to self-manage diabetes mellitus through a community-based health screening, education, and mentoring approach. The